Hiv and AIDS in rural Tonga culture - Ncube, Vincent (HTS teologiese studies, 2016)
Thirty-five years has gone by since the first diagnosis of HIV in Zimbabwe. Causes and reasons for the disease and its spread vary from place to place and from society to society. In some cases, the usage of needles and other medical apparatus is blamed for causing the disease. In some other instances, some religious beliefs are held responsible for the pandemic. However, it is a different case with the Tonga females of the Pashu community in Zimbabwe. The belief is that HIV among the Tonga females is perpetuated by some cultural practices and beliefs. The practices and beliefs pose a danger to the lives of the Tonga females from the age of infancy to that of elderly women. The culture of silence, loyalty and submissiveness has even aggravated the suffering of these people. The culture has denied them an opportunity to seek medical aid and pastoral therapy. Hope for life and a future for these people are inevitably lost. The study is, therefore, an effort to validate the assumed claim that the Tonga females are exposed to HIV by some of the cultural practices. It is also the purpose of this study to create a pastoral care methodology which will be used to view the problem from a pastoral perspective. A review of the alleged cultural practices is also the business of this study.